Influence of the Economic Transformation on the Social Sphere in Poland after 1989 (Economic and Political Thought, 2010)
The end of the era of communism in Poland initiated a period ofenormous systematic changes which led to the establishment of democracyand introduction of market economy. The transformation of the economicsystem meant a thorough reform of the Polish economy through substitutionof central planning by free market mechanisms. This caused changes not onlyin the sphere of production but also within the distribution of wealth and inthe social sphere.The present article is intended to examine the influence of the economictransformation in Poland on the social sphere after 1989. As a researchmethod it uses a theoretical analysis of selected publications and Internetresource materials. In the first part of the article the author presents theorigin of the Polish systematic changes started in the late 1980s. Next themain areas of economic changes are characterized. In the final part of thearticle the author analyses social changes resulting from the introducedeconomic reforms.